Quality of Life of Patients Undergoing Maintenance Hemodialysis in Erbil City - Haval Mohammed Qader; Vian Afan Naqshbandi (Hawler Medical University, 2019)
Background and objectives: Chronic renal disease is one of the developing issues every-where throughout the world. Health-related quality of life is critical, yet is disregarded part of chronic kidney disease care. Alongside survival and different kinds of clinical results, patient quality of life is an important marker of the effectiveness of the medical care they get. The study aimed to evaluate the quality of life of patients undergoing maintenance hemodialysis in Erbil city. Methods: A descriptive study design conducted in the Erbil Dialysis Centre and Dialysis unit at Erbil Teaching Hospital. The sample include 262 end-stage renal failure patients undergoing hemodialysis for at least 2 months, the Kidney Diseases Quality of Life short form questionnaire were used to obtain the information through structured interview. The study lasted from 24 March to 30 May 2018. The data were analyzed through descriptive statistical approach, chi-square test and person correlation analysis. Results: Participants were 262 patients with mean age of 55.55 ±13.831 years, 52.3% were female, 92% were married, 46.2% were illiterate and 66.4% were from rural area. The overall Quality of Life score was higher in male patients than female. About 61% of patients had below average Quality of Life. Regarding the Quality of Life domains, out of seven domains only two of them (symptoms/ problems and quality of social interaction domains) were at average level of quality of life, the rest domains were below average level. The results of the study revealed that there is significant relationship between Quality of Life score and level of education. Conclusion: According to the finding of the study, the patients with end-stage renal failure undergoing hemodialysis had poor Quality of Life in most domains and the study found that there were a significant relationship between patients education and there quality of life.